2010
DOI: 10.4322/actalb.02202003
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic macrophytes in natural and managed wetlands of Rio Grande do Sul State, Southern Brazil

Abstract: Aim: This study gathers the main results obtained from studies regarding dynamic of aquatic macrophyte community in natural and managed wetlands of Southern Brazil. We analyzed the aquatic macrophytes diversity in wetlands of Southern Brazil, the environmental factors that determine the structure of the aquatic macrophyte community in fragmented wetlands, the effects of floods on the dynamics of macrophytes, and the contributions to the rice field for the conservation of aquatic macrophytes; Methods: The infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
2
13
0
10
Order By: Relevance
“…Irgang e Gastal (1996) relataram a existência de 331 espécies de macrófitas nos diversos tipos de áreas úmidas estuarinas, ripári-as lacustres e palustres) da Planície Costeira do sul do Brasil. No entanto, considerando apenas as áreas úmidas palustres, em sistemas similares aos enfocados no presente estudo, foi relatada a presença de cerca de 250 espécies de macrófitas nas áreas úmidas do Rio Grande do Sul (Rolon et al, 2010). O presente estudo contribuiu para ampliar o conhecimento sobre a diversidade de macrófitas do Parque Nacional da Lagoa do Peixe, a qual era conhecida apenas para o sistema estuarino e mata paludosa (Dorneles e Waechter, 2004;Knak, 2004).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Irgang e Gastal (1996) relataram a existência de 331 espécies de macrófitas nos diversos tipos de áreas úmidas estuarinas, ripári-as lacustres e palustres) da Planície Costeira do sul do Brasil. No entanto, considerando apenas as áreas úmidas palustres, em sistemas similares aos enfocados no presente estudo, foi relatada a presença de cerca de 250 espécies de macrófitas nas áreas úmidas do Rio Grande do Sul (Rolon et al, 2010). O presente estudo contribuiu para ampliar o conhecimento sobre a diversidade de macrófitas do Parque Nacional da Lagoa do Peixe, a qual era conhecida apenas para o sistema estuarino e mata paludosa (Dorneles e Waechter, 2004;Knak, 2004).…”
Section: Discussionunclassified
“…O presente estudo contribuiu para ampliar o conhecimento sobre a diversidade de macrófitas do Parque Nacional da Lagoa do Peixe, a qual era conhecida apenas para o sistema estuarino e mata paludosa (Dorneles e Waechter, 2004;Knak, 2004). O elevado número de espécies das famílias Cyperaceae, Poaceae, Juncaceae e Asteraceae encontrado nesse estudo foi similar ao verificado em outros estudos sobre a composição de plantas aquáticas de áreas úmidas (Pott e Pott, 1997;Mormul et al, 2010;Rolon et al, 2010). Além dessas famílias exibirem uma alta riqueza de espécies, os gêneros dessas famílias são frequentemente diversos entre as macró-fitas aquáticas (Henry-Silva et al, 2010).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The total number of AVPs that were used at the time of the study (16 species) represented 3 % of 500 species (Irgang & Gastal 1996) and 6 % of 250 species (Rolon et al 2010) that have been reported in the state of Rio Grande do Sul. This result suggests that although a high proportion of AVPs exist in one place, few are selected for handicraft use.…”
Section: Knowledge Of Aquatic Vascular Plants That Are Used For Handimentioning
confidence: 99%
“…The names of the plants recorded in this study were updated according to data from The Plant List database (www.theplantlist.org). The plants that were mentioned by interviewees as occurring in wetlands were classified as aquatic based on Irgang & Gastal (1996), Rolon et al (2010), and Alves et al (2015). Additionally, the Endangered Species List of Species of Flora of Brazil (Alves et al 2015) was consulted to note the state of threat as well as the origin and distribution of certain species.…”
Section: Data Collectionmentioning
confidence: 99%